Transient Tachypnea of the Newborn: Pathogenesis, Diagnosis, Treatment - Evgenii V. Shestak; Olga P. Kovtun ("Paediatrician" Publishers LLC, 2022)
The review provides up-to-date information on the development of transient tachypnea of the newborn (TTN) considering early postnatal period physiology and pathophysiological processes. Data on risk factors of TTN development, feature of disease course, and its differential diagnosis are presented. Traditional treatment methods for patients with TTN as well as results of modern studies on efficacy of non-invasive respiratory support are covered.